2019
DOI: 10.3390/vaccines7040188
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Socioeconomic Inequalities in Full Vaccination Coverage among Vietnamese Children Aged 12–23 Months, 2000–2014: Evidence for Mitigating Disparities in Vaccination

Abstract: There has been no report on the situation of socioeconomic inequalities in the full vaccination coverage among Vietnamese children. This study aims to assess the trends and changes in the socioeconomic inequalities in the full vaccination coverage among Vietnamese children aged 12–23 months from 2000 to 2014. Data were drawn from Multiple Indicator Cluster Surveys (2000, 2006, 2011, and 2014). Concentration index (CCI) and concentration curve (CC) were applied to quantify the degree of the socioeconomic inequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Although they were used mainly for national-level reporting, data from these surveys have the capacity to present progress of equity gaps in GAPPD indicators amongst subgroups within countries. Previous studies from Vietnam and Nepal using data from the DHS and MICS between 2000 to 2014, found national level improvements in immunisation coverage and health seeking behaviours for acute illnesses [38,39]. However, when the data was disaggregated by household socioeconomic status, geographical location, parental education and ethnicity, inequities amongst these subpopulations persisted over the 13 to 14-year period.…”
Section: Discussionmentioning
confidence: 91%
“…Although they were used mainly for national-level reporting, data from these surveys have the capacity to present progress of equity gaps in GAPPD indicators amongst subgroups within countries. Previous studies from Vietnam and Nepal using data from the DHS and MICS between 2000 to 2014, found national level improvements in immunisation coverage and health seeking behaviours for acute illnesses [38,39]. However, when the data was disaggregated by household socioeconomic status, geographical location, parental education and ethnicity, inequities amongst these subpopulations persisted over the 13 to 14-year period.…”
Section: Discussionmentioning
confidence: 91%
“…Neonatal BCG vaccination is included in the Expanded Program on Immunization, and coverage has been at a high level since 2009. In 2019, 95% of neonates in Vietnam received BCG, though vaccination rates were lower for children who were born in rural areas, in ethnic minority communities, or to mothers with low education [74]. The high BCG coverage will impact on severe disease in young children, but clinical diagnosis is an ongoing challenge as a reliance on bacteriological confirmation results in under-detection, especially among high-risk young children [75].…”
Section: Vietnam: Where Are the Child Tb Cases?mentioning
confidence: 99%
“…It is assumed that health insurance is influenced by other specific attributes of the families in which the individuals are born. It has been argued that many socio-economic disparities are accountable for accessing childhood healthcare services ( 25 ). For instance, the education of the population ( 35 ), especially the mother's level of education ( 23 ), is crucial.…”
Section: Covariates Of Health Insurancementioning
confidence: 99%
“…For instance, the education of the population ( 35 ), especially the mother's level of education ( 23 ), is crucial. Many researchers posited that education is vital in providing more efficient health inputs to children ( 25 27 ). The research reflects that educated mothers may pay for the optimum preventative care by visiting doctors, thereby more effectually averting serious diseases ( 28 ).…”
Section: Covariates Of Health Insurancementioning
confidence: 99%
See 1 more Smart Citation